Workplace‐Based Education Interventions for Managing Metabolic Syndrome in Low‐ and Middle‐Income Countries: A Realist Review - Sitotaw Kerie Bogale; Haribondhu Sarma; Tilahun Tewabe Alamnia; Matthew Kelly (Wiley, 2024)
ABSTRACT Background Sedentary office work and work‐related stress increase the risk of metabolic syndrome. Workplace‐based education interventions for promoting prevention are gaining popularity due to their positive impact on managing metabolic syndrome. We conducted this realist review to understand the contextual factors and mechanisms that contribute to the effectiveness of these interventions and how they interact to produce outcomes. Method We conducted a comprehensive search of five main databases (PubMed, Web of Science, ProQuest, Scopus and PsycINFO) and Google Scholar, as well as references of included articles. We included all studies published until 12 January 2023, reporting the effects of workplace lifestyle education interventions on metabolic syndrome. Using a realist review approach, we identified and evaluated middle‐range theories to develop a context-mechanism-outcome configuration. Results We identified 6883 titles for screening, of which 15 studies were included in this realist review. This realist review has identified strong social support networks, workplace influence, involvement of worksite managers and cultural relevance as contextual factors that contribute to the effectiveness of workplace‐based education interventions for managing metabolic syndrome in low‐ and middle‐income countries, which may not be as prominent in developed countries. Conclusion The review concludes that while developing and implementing healthy lifestyle policies in the workplace, policymakers and researchers should consider social support, workplace influences, manager participation and cultural relevance.